Structural and Optical Properties of Diluted Magnetic Ga1−xMnxAs–AlAs Quantum Wells Grown on High-Index GaAs Planes - Gunes, Mustafa; Gumus, Cebrail; Galvao Gobato, Y.; Henini, M. (Indian Academy of Sciences, 2017)
We report on the structural and optical properties of Ga₁₋ᵪ Mn ᵪ As-AlAs quantum wells (QWs) with χ=0.1% grown by molecular beam epitaxy (MBE) on semi-insulating GaAs substrates with orientations (100), (110), (311)B and (411)B. Atomic force microscopy (AFM), X-ray diffraction (XRD) and photoluminescence (PL) techniques were used to investigate these QWs. AFM results have evidenced the formation of Mn-induced islands, which are randomly distributed on the surface. These islands tend to segregate for samples grown on (110) and (411)B planes, while no clear segregation was observed for samples grown on (100) and (311)B orientations. Results show that the PL line width increases with Mn segregation. XRD measurements were used to determine 2θ,d and cell parameters.